Maintenance decision-making for power generating unit in thermal power plant using combined fuzzy AHP-TOPSIS approach. (2017) - Panchal, Dilbagh; Kumar, Dinesh
Selection of an optimal maintenance strategy is one of the biggest challenges maintenance managers face. This paper seeks to suggest an optimal maintenance strategy for power generating unit (PGU) of a coal fired thermal power plant by applying combined fuzzy AHP-fuzzy TOPSIS approach. Maintenance decision-making is a multi-criteria decision-making (MCDM) problem where qualitative information received from experts is converted into quantitative form. Triangular fuzzy numbers (TFNs) are used to account for the uncertainty/imprecision in human judgment. Weights related to criteria and sub criteria are computed using fuzzy analytical hierarchy process (AHP) approach while final selection of maintenance strategy is done by applying fuzzy technique for order preference by similarity to ideal solution (TOPSIS) approach. Sensitivity analysis is carried out to monitor robustness of maintenance strategy with change in sub-criteria weights. Results will be shared with the plant maintenance manager to implement the maintenance strategy determined in this paper for improving system availability and minimising operative cost.